The relationship between firms’ corporate social performance and green technology innovation: The moderating role of slack resources1 - Xie, Yi (Frontiers in Environmental Science, 2022)
This study explores the relationship between firms’ corporate social responsibility (CSR) and their “green” technology innovation in the context of a developing country with a high level of economic growth (China). Using data from listed companies, green patent authorization data from the State Intellectual Property Office, and social responsibility rating data from Rankin’s CSR Ratings of China from 2009 to 2017, we find that a higher CSR rating is highly positively correlated to green technology innovation as measured by number of green patents granted. Results indicated that corporate social performance plays a contributory role in green technology innovation. We also find that unabsorbed slack resources enhance the positive relationship between CSR rating and the number of green technology patents.